How to make an effective logo - Shylo, Lela; Kovalchuk, Olga (My University, 2014)
A company’s logo is a recognition tool for the public to link their services or products to the company. In other words, it is part of a company’s branding. Without such branding, the public will not be able to differentiate between companies, and therefore unable to expect a certain standard or quality from the company which they interact with. A logo, if designed effectively, can bring to people’s mind the unique selling proposition of an organization, which inevitably promotes the company on a sub-conscious level.
Keywords: logo; business; branding; логотип; бізнес; брендинг; кафедра ділової іноземної мови та міжнародної комунікації